Cover Feature: From Bowls to Capsules: Assembly of Hexanuclear NiII Rings Tailored by Alkali Cations (Chem. Eur. J. 49/2020). Issue 49 (7th August 2020) - Mayans, Júlia; Stoumpos, Constantinos C.; Font‐Bardia, Mercé; Escuer, Albert
Abstract : The increase of the radius of the alkali cations from Li + to Cs + and the size of their coordination sphere determine the transition between supramolecular capsules to bowls, built by assembly of Ni6 metallacycles. Noteworthy, the NR4 + countercations linked to exo ‐binding sites becomes crucial to stabilize the multicomponent supramolecules. More information can be found in the Full Paper by A. Escuer et al. on page 11158 .